Research on indicator system and carbon emissions of lowcarbon eco-city - A case study in Hangzhou, China - J. Ge; M.Y. Lu; J. Lu; X.Y. Luo; Y. Zhu (Lowland Technology International, 2017)
Based on an extensive review of 31 international and domestic indicator systems, a system, which consists of 6 primary categories, 19 secondary categories, and 39 indicators is proposed for Transfer Science and Technical Park in Hangzhou city, covering sustainable development in environment, urban space and green building, transportation, energy and resource, governance and infrastructure, and economy aspects. Then all indicators are classified into three implementation stages (e.g. regional control indicators, park management indicators, and block control indicators) to ensure the fully accomplishment of low-carbon targets, which are always neglected by researchers, planners, governments and city managers. In the end, two scenarios are adopted, while the former is developing in traditional way and the latter is under the circumstance that all indicators are accomplished, to calculate the carbon reduction in order to quantitatively evaluate the effect of the indicator system. The results reveal that the policy makers should give the priority to indicators related to green buildings (e.g. ratio of green buildings), utilization of renewable energy, green transportation (e.g. mixed land use, green travel, green vehicles, etc.), greenery (green coverage ratio, multi-coat landscaping planting system etc.) while establishing policies and guidance towards a low-carbon eco-city.